2019
DOI: 10.1177/1352458519828663
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous multiple cervical artery dissections after alemtuzumab

Abstract: We report a case of multiple cervical artery dissections that occurred 4 days after a first course of alemtuzumab in a woman with relapsing–remitting multiple sclerosis and discuss its potential relationship and mechanisms of action. In particular, an arterial inflammatory process, secondary to cytokine release, could potentially lead to intimal thickening, luminal irregularities, stenosis, and ultimately occlusion. Occurrence of an unexpected serious adverse event, in our case, multiple cervical artery dissec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
12
0
1
Order By: Relevance
“…This approach has been proposed by several published expert opinions and treatment guidelines including those published by the Association of British Neurologists and the Italian Society of Neurology [90,91]. Another important factor that supports delaying treatment in infected patients or who are at high risk of catching the infection is the link between alemtuzumab and the risk of stroke and cervicocephalic arterial dissection [92,93]. This might augment the COVID-19-related risk of thrombosis and intracerebral hemorrhage [94] if patients are re-dosed with alemtuzumab during infection or if they catch the infection shortly after redosing.…”
Section: Potential Relevance To the Covid-19 Pandemic And Possible Rimentioning
confidence: 99%
“…This approach has been proposed by several published expert opinions and treatment guidelines including those published by the Association of British Neurologists and the Italian Society of Neurology [90,91]. Another important factor that supports delaying treatment in infected patients or who are at high risk of catching the infection is the link between alemtuzumab and the risk of stroke and cervicocephalic arterial dissection [92,93]. This might augment the COVID-19-related risk of thrombosis and intracerebral hemorrhage [94] if patients are re-dosed with alemtuzumab during infection or if they catch the infection shortly after redosing.…”
Section: Potential Relevance To the Covid-19 Pandemic And Possible Rimentioning
confidence: 99%
“…These encompass acute cardiovascular events such as acute coronary artery syndrome or myocardial ischemia, as well as ischemic and hemorrhagic strokes. 810…”
mentioning
confidence: 99%
“…Durand-Dubief et al reported a case of multiple cervical arterial dissections days after treatment with alemtuzumab. 1 Five cases of intracerebral haemorrhage were recently reported by Azevedo et al 2 In November 2018, this concern prompted the United States Food and Drug Administration (FDA) to add the risk of stroke within three days of administration to the boxed warning on the drug's label. 3 The FDA commented on the possible causative role of cytokine release syndrome, but decided there was insufficient evidence.…”
Section: Highlightsmentioning
confidence: 99%